Combined treatment in Ramsay Hunt syndrome: evaluation of clinic and prognosis - Pınar, Ercan; İmre, Abdulkadir; Olgun, Yüksel; Ata Ece, Ahmet; Songu, Murat; Aslan, Hale (ENT Updates, 2014)
Objective: We retrospectively analysed clinical characteristics, treatment and outcomes of the patients with Ramsay Hunt syndrome. Methods: Twelve patients with Ramsay Hunt syndrome were analysed retrospectively. Data recorded included sex, age, time from first onset to initial treatment and clinical outcomes. The House-Brackmann scale was used to assess initial facial nerve dysfunction and final facial nerve impairment. All patients were treated with oral steroids and oral acyclovir. Results: There were 7 male and 5 female patients. Mean age was 59 (range: 21 to 68) years. The main symptom was acute facial palsy. House-Brackmann classification of facial nerve function ranged from grade III to VI before treatment. The median baseline House-Brackmann grade was 4.5 and it was 2.33 after the treatment in all patients. Recovery rate of facial palsy was lower in patients with House-Brackmann grades V and VI. Conclusion: In this syndrome, the prognosis of facial palsy depends on the initial symptoms and clinical findings. The prognosis was poorer in severe palsy and patients with comorbid disease(s).